Rio de Janeiro residents perceptions of the 2016 Olympics in the pre-Games period - Zouain,Deborah Moraes (2019)
Between 2014 and 2016, the city of Rio de Janeiro hosted two mega- sporting events: the FIFA World Cup and the Olympics, generating changes in the city. This study aims to analyze the perceptions of Rio residents in the lead-up to the Games. A quantitative survey was conducted face-to-face with a sample of 404 residents, precisely one year before the Olympics. The data indicate that the period before the Games was troubling for residents in light of uncertainties regarding the desired Olympic legacy for the city. In fact, residents routines were impacted, either by transit issues or by media reports that generated expectation and apprehension. The pre-Olympic period was marked by protests, concern about overspending, construction delays and fear about the success of the mega-event. However, in the perception of residents, an evident expectation was the legacy to tourism, the visibility of the destination and lasting improvements for tourism and sport.